2019
DOI: 10.1039/c9cp03283e
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gold nanoparticles on the two photon absorption of photochromic molecular systems

Abstract: In this study, we investigate the influence of gold nanoparticles on the nonlinear optical properties of the dihydroazulene/vinylheptafulvene photo- and thermochromic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…[54][55][56][57][58][59] The electronic polarizabilities of the nanoparticles ensure that the excited states of formaldehyde are interacting with the appropriate polarization of the nanoparticle as demonstrated previously. [54][55][56][57][58][59] The TiO 2 NP is modelled using the rutile structure of TiO 2 . The lattice parameters of the unit cell are a = b = 4.594 Å and c = 2.959 Å and the most commonly occurring (110) surface has been utilized.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…[54][55][56][57][58][59] The electronic polarizabilities of the nanoparticles ensure that the excited states of formaldehyde are interacting with the appropriate polarization of the nanoparticle as demonstrated previously. [54][55][56][57][58][59] The TiO 2 NP is modelled using the rutile structure of TiO 2 . The lattice parameters of the unit cell are a = b = 4.594 Å and c = 2.959 Å and the most commonly occurring (110) surface has been utilized.…”
Section: Methodsmentioning
confidence: 83%
“…Previously, we have successfully used this approach when investigating organic photochromic molecules interacting with metallic nanoparticles. 54–59 The electronic polarizabilities of the nanoparticles ensure that the excited states of formaldehyde are interacting with the appropriate polarization of the nanoparticle as demonstrated previously. 54–59…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…18 Furthermore, we found that the NPs can enhance both one and two photon absorption of these systems while also providing significant redshifts in the absorption and clear alterations in the electric properties. [19][20][21] Hence, the coupling of such NPs to the NBD/QC system could be used as catalyst for the thermal back reaction while also possible tuning optical properties for solar energy storage.…”
Section: Introductionmentioning
confidence: 99%